Financial Performance Analysis of Distressed Banks in Ghana: Exploration of Financial Ratios and Z-score - MATEY, Juabin (Journal of Advanced Studies in Finance; Vol 12 No 1 (2021): JASF Volume XII Issue 1(23) Summer 2021, 2021)
Abstract : A healthy bank sector is critical to an economy's stability. This is illustrated by most countries' concentration on macroeconomic policies affecting the banking industry. In 2017, the Ghanaian bank industry underwent a clean-up exercise to rehabilitate the industry's impaired operating environment, which was exacerbated by an unmanageable rate of non-performing loans and a deficient tier one capital base. To assess the soundness of the affected institutions, this study used financial ratios and the Z-score to examine UT Bank’s financial performance prior to the 2017 bank industry health check. Annual financials for a ten-year period (2007–2016) were analyzed. UT Bank's debt management policies were found to be deficient. This was evident in the underwhelming leverage and risk management variable ratios. It was clear that UT Bank had difficulty meeting its debt obligations to creditors. 7.6 debt-to-equity and 0.90 debt-to-asset ratios indicated a precarious condition. Credit management strategies at UT Bank and other banks that experienced these challenges in the industry must swiftly be improved to safeguard customer deposits. As a policy recommendation, the regulator of the banking industry (the Bank of Ghana) should bolster its supervisory and monitoring functions to aid in the early detection of non-performing banks. Additionally, this paper advises that banks' statutory lending limits of 10% for unsecured loans and 25% for secured loans of banks' net owned funds be maintained.